The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/hbm.22926
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Alzheimer's disease signature in MR images seven years before conversion to dementia: Toward an early individual prognosis

Abstract: Finding very early biomarkers of Alzheimer's Disease (AD) to aid in individual prognosis is of major interest to accelerate the development of new therapies. Among the potential biomarkers, neurodegeneration measurements from MRI are considered as good candidates but have so far not been effective at the early stages of the pathology. Our objective is to investigate the efficiency of a new MR-based hippocampal grading score to detect incident dementia in cognitively intact patients. This new score is based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 51 publications
8
60
0
Order By: Relevance
“…We previously showed that using only SNIPE scores for hippocampus, plus age and sex, one can reach an overall accuracy of 71% for prediction of progression from MCI to dementia over a 3y follow-up period [11]. In a more recent work looking at a cohort of cognitively healthy older individuals, we showed that our MR-driven SNIPE biomarker was sensitive to AD-related changes in a cognitively normal cohort on average seven years before clinical diagnosis of AD dementia [13].…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…We previously showed that using only SNIPE scores for hippocampus, plus age and sex, one can reach an overall accuracy of 71% for prediction of progression from MCI to dementia over a 3y follow-up period [11]. In a more recent work looking at a cohort of cognitively healthy older individuals, we showed that our MR-driven SNIPE biomarker was sensitive to AD-related changes in a cognitively normal cohort on average seven years before clinical diagnosis of AD dementia [13].…”
Section: Introductionmentioning
confidence: 77%
“…Hippocampal and entorhinal SNIPE grading scores were used as the only MRI biomarker features in the predictive classifier. The SNIPE score is described fully in [13,20]. In short, SNIPE assigns a similarity metric to each voxel, which shows how much that voxel's neighbourhood resembles the anatomy of either a group of patients with Alzheimer's dementia or a group of normal controls.…”
Section: Mr Derived Biomarkermentioning
confidence: 99%
See 1 more Smart Citation
“…While this could be an important undertaking in the context of the hippocampal volume segmentation, such analyses are a topic of hot debate in the literature (Coupe et al, 2011a; Coupe et al, 2015; Eskildsen et al, 2013; Davatzikos et al, 2011; Wang et al, 2010). Such a problem would require several design choices, which themselves will be controversial, each of which could easily account for a source of detailed investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The disease processes leading to AD are known to start while individuals are still cognitively normal and may precede clinical symptoms by years or decades (Jack et al, 2010, Adaszewski et al, 2013). Reflecting this and the call for the biological evidence for AD diagnosis, several AD specific biomarkers have been identified, including multivariate patterns of structural brain atrophy measured by magnetic resonance imaging (MRI) (Moradi et al, 2015, Bron et al, 2015, Salvatore et al, 2015, Coupé et al, 2015, Eskildsen et al, 2013, Wee et al, 2013). MRI-based biomarkers have the advantages of being non-invasive and widely available.…”
Section: Introductionmentioning
confidence: 99%